The Marketplace for New Caries Management Products: Dental Caries Detection and Caries Management by Risk Assessment - Berg Joel H (BMC Oral Health, 2006)
Abstract The number of new technologies emerging each year in the realm of dental caries management is growing at an exponential rate. Examining the patent literature, one can see that this growth rate will likely continue, with the outcome that dentistry will see an expanded growth in managing dental caries by risk assessment with medicinal therapeutic interventions. Restorative dentistry solutions, treating the results of dental caries, will continue to grow, while technologies to identify the caries process at its earliest stages will soon invade practices everywhere. The most interesting aspect of these changes will be how industry responds to the inexorable, yet slow change in dental professional demand for these new technologies, while trying to be the "first to market" within the various categories of this business opportunity. This paper will take a close look at how businesses with the core competence to be key players in this emerging growth category will assess the marketplace, and match up their business interests with the changing needs of the dental profession. The paper will also address the strategic planning and business processes that the dental industry will undertake to bring new technologies to market, and how these technologies will be positioned to health care professionals and consumers. The results of the key interactions between industry and the dental profession will determine the extent to which dental caries is managed as a disease, in addition to being managed by surgical restorative interventions.